The Christian God - Swinburne, Richard (Oxford University Press, 1994)
This book is about what it is for there to be a God, and why we might suppose that God to be the traditional Christian God. It analyses the metaphysical categories needed for this purpose and sets out ways in which the doctrine that there is a divine individual (an individual with the traditional divine properties) can be developed.